Investigating the effect of virtual preparation programs to empower students in comprehensive exams based on Crickpatrick\'s evaluation model. - Samaneh Jafari; Maryam Ghaemi Amiri; Hanie Yavarpour; Mohammad Mahdi Mahmoodjanloo; Zeinab Pouralijan Amiri (Babol University of Medical Sciences, 2023)
Background and Objective: The basic science comprehensive exam is held every year at the end of the basic science course as a license to enter the next stage, and the results of each course represent the quality of education in that educational group. Considering the expansion of the use of educational virtual programs in Babol University of Medical Sciences, the aim of this research is to investigate the impact of virtual programs in preparing medical students for empowerment in comprehensive exams based on Crickpatrick's evaluation model. Methods: This descriptive and analytical research was cross-sectional and was conducted on 317 medical students of Babol University of Medical Sciences in 1399-1400. Students answered a researcher-made questionnaire about the quality of virtual preparation programs. The reliability and validity of the questionnaire was evaluated. The reliability and validity of the questionnaire was evaluated. Finally, the data obtained from the questionnaire was entered into the SPSS V.20 software. Findings: The validity and reliability of the questionnaire was confirmed by evaluating the indexes CVR and CVI. In general, the students declared the effectiveness of preparation programs for comprehensive exams to a high extent and with 81.6% satisfaction. Conclusion: Considering that the degree of satisfaction with the virtual programs for preparing medical students to participate in the comprehensive exam is very high, therefore, these programs can be used to improve the learning of students of other universities and also by simulating for other fields.